2021
DOI: 10.2147/rmi.s292314
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Predicting Clinical Outcome in COVID-19 Patients from Clinical, Biochemical and a Qualitative Chest X-Ray Scoring System

Abstract: Purpose: To determine the performance of a chest radiograph (CXR) severity scoring system combined with clinical and laboratory data in predicting the outcome of COVID-19 patients. Materials and Methods: We retrospectively enrolled 301 patients who had reverse transcriptase-polymerase chain reaction (RT-PCR) positive results for COVID-19. CXRs, clinical and laboratory data were collected. A CXR severity scoring system based on a qualitative evaluation by two expert thoracic radiologists was defined. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Another AI-based model was designed to see how well a chest radiograph performs through scoring of the severity of COVID-19. The model was integrated with laboratory and clinical evidence to predict the outcomes of COVID-19 for infected patients [ 75 ]. The obtained results showed an accuracy of 84% and AUC = 0.82.…”
Section: Discussionmentioning
confidence: 99%
“…Another AI-based model was designed to see how well a chest radiograph performs through scoring of the severity of COVID-19. The model was integrated with laboratory and clinical evidence to predict the outcomes of COVID-19 for infected patients [ 75 ]. The obtained results showed an accuracy of 84% and AUC = 0.82.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors proposed the use of severity score indexes for the evaluation of CXR, based on the type and extension of lung alterations, and demonstrated that higher scores correlated with worse clinical conditions and outcomes. More extended consolidations on initial CXR are associated with a higher rate of hospitalization and invasive mechanical ventilation [ 9 , 16 ▪ , 19 , 20 ].…”
Section: Chest X-raymentioning
confidence: 99%
“…3a and b). Interestingly, Artificial Intelligence models have been applied to CXRs with the aim of improving diagnostic accuracy and lowering the need of human workforce during the pandemic [9,22].…”
Section: Chest X-raymentioning
confidence: 99%
See 1 more Smart Citation
“…Chest radiographs are insensitive in early and mild Covid-19 infections and are usually used as a first line tool in the triage of patients in the emergency department. 18,20 Nevertheless, chest radiography has an advantage over computed tomography of being readily available, cheaper, portable with a lower radiation dose. They also aid in the assessment of the disease progression and in detecting other diseases contributing to the patients symptoms.…”
Section: Introductionmentioning
confidence: 99%